2012
DOI: 10.7874/kja.2012.16.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isoflurane on the Hearing in Mice

Abstract: Background and ObjectivesThe aim of this study was to investigate the relationship between inhalation anesthetics and hearing in mice.Materials and MethodsAs inhalation anesthetics, isoflurane was used. Auditory brainstem response and distortion product otoacoustic emission were used as measurement of hearing. Mice were divided into 2 groups. 'Isoflurane group' consisted of mice that were anesthetized with an inspired concentration of 2.0 vol% isoflurane with 2 L/min of oxygen (n=10). 'Control group' consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Our results demonstrate that, in the mid-to high range tones of the cochlea (i.e., 9.2–32 kHz), DPOAE thresholds obtained under isoflurane anesthesia were significantly elevated compared to those obtained under ketamine/xylazine anesthesia. Similarly, Kim and colleagues observed poorer DPOAE thresholds across all frequencies in mice anesthetized with isoflurane (Kim et al, 2012 ). Data obtained by Sheppard colleagues in Sprague-Dawley rats also reported that usage of isoflurane anesthesia could significantly reduce DPOAE amplitudes relative to ketamine/xylazine (Sheppard et al, 2018 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Our results demonstrate that, in the mid-to high range tones of the cochlea (i.e., 9.2–32 kHz), DPOAE thresholds obtained under isoflurane anesthesia were significantly elevated compared to those obtained under ketamine/xylazine anesthesia. Similarly, Kim and colleagues observed poorer DPOAE thresholds across all frequencies in mice anesthetized with isoflurane (Kim et al, 2012 ). Data obtained by Sheppard colleagues in Sprague-Dawley rats also reported that usage of isoflurane anesthesia could significantly reduce DPOAE amplitudes relative to ketamine/xylazine (Sheppard et al, 2018 ).…”
Section: Discussionmentioning
confidence: 84%
“…A study performed in rats also showed significantly elevated ABR threshold among all frequencies tested (ranging from 8 to 32 kHz) under isoflurane anesthesia relative to ketamine/xylazine anesthesia with the greatest threshold shift found in the region between 12 and 24 kHz (Ruebhausen et al, 2012 ). In contrast, Kim and colleagues found no differences between ABR baseline recordings using BALB/c mice (Kim et al, 2012 ). Our study revealed a significant reduction in wave I amplitude when isoflurane anesthesia was used.…”
Section: Discussionmentioning
confidence: 95%